An Investigation of Interoceptive Sensitivity in Eating Disorders Using a Heartbeat Detection Task and a Self‐report Measure. (1st July 2014) - Eshkevari, Ertimiss; Rieger, Elizabeth; Musiat, Peter; Treasure, Janet
Abstract Background Interoception has been proposed to play an important role in the pathogenesis of eating disorders (EDs). Objective The aim of this study was to examine a heart beat detection task (HBDT) as an objective index of interoceptive sensitivity in individuals with an ED. Method The self‐report interoceptive deficits subscale of the Eating Disorders Inventory 3 was also used. Results The results of the HBDT demonstrated no significant difference between individuals with an ED and healthy controls. However, performance on this task also did not appear to be different from that expected by chance. Thus, these results cast doubt on the utility of the present HBDT for measuring interoceptive sensitivity. Conclusion Overall, the findings indicate that further research is needed to develop valid, objective measures of interoceptive sensitivity to be used in EDs, so as to overcome the reliance on the Eating Disorders Inventory 3 self‐report subscale and to determine how such measures relate to ED and general psychopathology. Copyright © 2014 John Wiley & Sons, Ltd and Eating Disorders Association.